Iron Deficiency Anemia in Inflammatory Bowel Disease: What Do We Know? - Resál, Tamás; Farkas, Klaudia; Molnár, Tamás (Frontiers in Medicine, 2021)
One of the most common extraintestinal manifestation of inflammatory bowel disease is iron deficiency anaemia. It is often an untreated condition, that significantly impairs patients' quality of life, elevates mortality and morbidity. Although it is often accompanied by mild symptoms (eg fatigue, lethargy), it can provoke severe health conditions, like dyspnoea, palpitation, angina and mental disorders, and increases hospitalization and mortality rate as well. Since anaemia develops through several pathomechanisms, such as occult bleeding, chronic inflammation, medicines (eg methotrexate), treating anaemia effectively requires to manage the underlying pathological changes as well. Based on international publications and data, it is a frequent condition, and more frequent in paediatrics. According to Goodhand JR et al, iron deficiency is present in more than 60% of children, while only 14% of them received oral iron therapy. Compared to adult patients, 22% have iron deficiency, and 48% of them received oral and 41% intravenous iron therapy. Miller SD et al also highlighted that among young patients iron deficiency anaemia is a frequent condition, as almost 50% of the patients were anaemic in their cohort. European Crohn’s and Colitis Organisation’s statements are clear regarding the diagnosis of iron deficiency anaemia, and the iron supplementation as well. Third generation parenteral iron supplementations seem to be safer and more effective, than oral iron pills. Oral iron in many cases cannot replace the iron homeostasis as well, furthermore, it can provoke dysbiosis, which can potentially lead to relapse. As a result, we claim, that both oral and parenteral should be used more frequently, furthermore, intravenous iron could replace oral medicines as well, in certain cases. Despite the fact, that iron deficiency anaemia is examined by many aspects, further questions can be raised. Can it imply to underlying pathological lesions? Both oral and intravenous iron therapy are safe and effective? When, and how to use them? We demand, that more studies should be conducted regarding these issues.